Rare bird documentation form for Greater Scaup at Cedar Lake, 1982 - Schaufenbuel, Joseph P.et al (1982)
Rare bird documentation form for four Greater Scaups at Cedar Lake at Nashua, in Chickasaw County, IA on April 12, 1982. Epson - sheet feed